¿Está relacionado el tamaño de la empresa con la salud general y mental de sus trabajadores? - Martín del Río, Beatriz (2018)
Background: The perception of the relationship between work and health seems to be associated with organizational dimensions. The insight by workers that work affects progressively their health increases with the rise of the number of employees (INSHT, 2007), and the consideration of work as a cause of 'stress, anxiety or nervousness' (INSHT, 2011), as well as the frequent cases of stress in their jobs (EU-OSHA, 2013). Objective: To verify if the size of the company of ownership influences the workers' health. Method : A descriptive correlational design was used. They were studied the differences in two variables, general and mental health, depending on the size of the company. The sample consisted of 2165 workers (67% men, M age = 38.9 years) of 390 companies in Valencian Comunity in Spain. They were divided into three groups depending on the size of the company: Micro company (1-9 workers); Small company (10-49 workers); and Medium company (50249 workers). The SF-36 questionnaire was used to measure general health. The differences in health were analyzed according to the size of the company, using the Kruskal-Wallis test, and the MannWhitney test to establish the direction and magnitude of these differences. Results: Significant differences were obtained in the assessment of general and mental health by the workers, according to the size of the company. In addition, it was confirmed, as the larger the company was, the worse perceived health, both general [H (2) = 7.7; p = .022], as mental [H (2) = 8.2; p = .017]. The workers of companies with 50 or more workers, evaluate their general health at a lower level than the employees of the smaller companies (micro U = 165027, p = .011, r = .07, and small U = 196096, p = .016, r = .07). The same was found for mental health, between the medium and the micro company (U = 166714, p = .006, r = .08). Conclusions: Depending on the size of the company, there are differences in the perception of health by the workers, both in general and mental health. The larger the size of the company, the lower is the perception of general and mental health by the workers.